Armstrong's handbook of management and leadership for HR : developing effective people skills for better leadership and management - Armstrong, Michael, 1928- (Philadelphia Kogan, 2016)
"In order to make an effective contribution, HR specialists have to be good at management, leadership, and developing themselves and others. In addition, they need to be aware of the management and business considerations that affect their work. Armstrong's Handbook of Management and Leadership for HR explores these three concepts, providing the essential practical knowledge to reach excellence as a manager. This updated fourth edition of Armstrong's Handbook of Management and Leadership for HR includes new information on managing diversity and cross-cultural management and managing virtual teams; extra case studies, business examples, interviews, and student activities"--
"To make an effective contribution, HR specialists have to be good at management, leadership and developing both themselves and others. They also need to be aware of the management and business considerations that affect their work. Armstrong's Handbook of Management and Leadership for HR: Developing Effective People Skills for Better Leadership and Management provides guidance on the processes of management and leadership with particular reference to what HR managers and aspiring managers need to know and do to make a difference. Written by renowned human resources expert and bestselling author Michael Armstrong, Armstrong's Handbook of Management and Leadership for HR covers in one volume the 'Leading, Managing and Developing People' and 'Developing Skills for Business Leadership' Chartered Institute of Personnel and Development (CIPD) modules. It includes numerous practical features such as case studies, practitioner interviews, exercises and clear learning objectives to aid learning. This is the essential book for HR students and professionals looking to broaden their skills and understanding relating to management and leadership. Supporting online resources include downloadable flashcards, slideshows, case studies and activities"--
Keywords: Management -- Handbooks, manuals, etc; Leadership -- Handbooks, manuals, etc; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Human Resources & Personnel Management